2016
DOI: 10.1242/jcs.177907
|View full text |Cite
|
Sign up to set email alerts
|

Correctors of mutant CFTR enhance subcortical cAMP–PKA signaling through modulating ezrin phosphorylation and cytoskeleton organization

Abstract: The most common mutation of the cystic fibrosis transmembrane regulator (CFTR) gene, F508del, produces a misfolded protein resulting in its defective trafficking to the cell surface and an impaired chloride secretion. Pharmacological treatments partially rescue F508del CFTR activity either directly by interacting with the mutant protein and/or indirectly by altering the cellular protein homeostasis. Here, we show that the phosphorylation of ezrin together with its binding to phosphatidylinositol-4,5-bisphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
(70 reference statements)
2
33
0
Order By: Relevance
“…Ezrin is associated with cystic fibrosis, and several investigators have reported its binding to F508del CFTR, which is the most common mutation associated with this disease. In primary cystic fibrosis airway cells, the phosphorylation of ezrin threonine-567 enhances its binding to F508del CFTR and the actin cytoskeleton, activates the cAMP/PKA pathway, and rescues the F508del CFTR-dependent chloride secretion (Abbattiscianni et al 2016). In human airway epithelial cells, the formation of the CFTR-ezrin complex increases the cAMP-mediated activation of CFTR (Ribas et al 2007).…”
Section: Ezrin Modulates Signal Transduction Pathwaysmentioning
confidence: 99%
“…Ezrin is associated with cystic fibrosis, and several investigators have reported its binding to F508del CFTR, which is the most common mutation associated with this disease. In primary cystic fibrosis airway cells, the phosphorylation of ezrin threonine-567 enhances its binding to F508del CFTR and the actin cytoskeleton, activates the cAMP/PKA pathway, and rescues the F508del CFTR-dependent chloride secretion (Abbattiscianni et al 2016). In human airway epithelial cells, the formation of the CFTR-ezrin complex increases the cAMP-mediated activation of CFTR (Ribas et al 2007).…”
Section: Ezrin Modulates Signal Transduction Pathwaysmentioning
confidence: 99%
“…The most prevalent mutation, DF504, results in improper trafficking of the CFTR, owing to its misfolding, leading to a defect in Cl 2 secretion. As might be expected, CFTR interacts with many members of the trafficking protein complexes mentioned above, such as PDZ domain -containing proteins (Short et al 1998;Moyer et al 1999Moyer et al , 2000Sun et al 2000a;Karthikeyan et al 2001;Naren et al 2003;Cheng et al 2004;Li et al 2005;Bossard et al 2007;Gee et al 2011;Arora et al 2014;Loureiro et al 2015;Lobo et al 2016), ezrin (Sun et al 2000a;Naren et al 2003;Li et al 2005;Loureiro et al 2015;Abbattiscianni et al 2016), clathrin adaptors (Bradbury et al 1994;Bradbury 2000, 2001a,b;Peter et al 2002;Collaco et al 2010;Cihil et al 2012), v-and t-SNARES (Peters et al 2001;Bilan et al 2013), Rab11 (Swiatecka-Urban et al 2007;Silvis et al 2009;Bilan et al 2013;Holleran et al 2013), andMyo5B (Swiatecka-Urban et al 2007) and -VI (Ameen and Apodaca 2007;Collaco et al 2010); some of these interactions may be cell-type-specific, but these will not be reviewed here. Rather the focus will be on amelioration of CF by drugs that may work at novel trafficking loci for CFTR (Zhang et al 2011;Hanrahan et al 2013;…”
Section: Cystic Fibrosis Transmembrane Regulator (Cftr)mentioning
confidence: 77%
“…The C-terminal phosphorylation of ERM proteins has been reported to be required for apical actin enrichment in epithelial cells (Hipfner, 2004;Roch et al, 2010;Abbattiscianni et al, 2016). In C. elegans, loss of erm-1 results in reduced apical actin levels in the intestine and in the excretory canal (Göbel et al, 2004;Bernadskaya et al, 2011;Khan et al, 2013).…”
Section: Phosphorylation Of T544 Controls Apical Actin Enrichment Andmentioning
confidence: 99%